DNA‐PKc inhibition overcomes taxane resistance by promoting taxane‐induced DNA damage in prostate cancer cells. Issue 14 (23rd July 2021) - Chao, Olivia S.; Goodman, Oscar B.
Abstract: Background: Overcoming taxane resistance remains a major clinical challenge in metastatic castrate‐resistant prostate cancer (mCRPC). Loss of DNA repair proteins is associated with resistance to anti‐microtubule agents. We propose that alterations in DNA damage response (DDR) pathway contribute to taxane resistance, and identification of these alterations may provide a potential therapeutic target to resensitize docetaxel‐refractory mCRPC to taxane‐based therapy. Methods: Alterations in DDR gene expression in our prostate cancer cell line model of docetaxel‐resistance (DU145‐DxR) derived from DU‐145 cells were determined by DDR pathway‐specific polymerase chain reaction array and immunoblotting. The PRKDC gene encoding DNA‐PKc (DNA‐dependent protein kinase catalytic unit), was noted to be overexpressed and evaluated for its role in docetaxel resistance. Cell viability and clonogenic survival of docetaxel‐treated DU145‐DxR cells were assessed after pharmacologic inhibition of DNA‐PKc with three different inhibitors—NU7441, LTURM34, and M3814. Response to second‐line cytotoxic agents, cabazitaxel and etoposide upon DNA‐PKc inhibition was also tested. The impact of DNA‐PKc upregulation on DNA damage repair was evaluated by comet assay and analysis of double‐strand breaks marker, γH2AX and Rad51. Lastly, DNA‐PKc inhibitor's effect on MDR1 activity was assessed by rhodamine 123 efflux assay. Results: DDR pathway‐specific gene profiling revealed significant upregulation of PRKDC and CDK7, and downregulation of MSH3 in DU145‐DxR cells. Compared to parental DU145, DU145‐DxR cells sustained significantly less DNA damage when exposed to etoposide and docetaxel. Pharmacologic inhibition of DNA‐PKc, a component of NHEJ repair machinery, with all three inhibitors, significantly resensitized DU145‐DxR cells to docetaxel. Furthermore, DNA‐PKc inhibition also resensitized DU145‐DxR to cabazitaxel and etoposide, which demonstrated cross‐resistance. Inhibition of DNA‐PKc led to increased DNA damage in etoposide‐ and docetaxel‐treated DU145‐DxR cells. Finally, DNA‐PKc inhibition did not affect MDR1 activity, indicating that DNA‐PKc inhibitors resensitized taxane‐resistant cells via an MDR1‐independent mechanism. Conclusion: This study supports a role of DDR genes, particularly, DNA‐PKc in promoting resistance to taxanes in mCRPC. Targeting prostatic DNA‐PKc may provide a novel strategy to restore taxane sensitivity in taxane‐refractory mCRPC.